Characterization and Function Analysis of β, β-carotene-9′, 10′-oxygenase 2 (BCDO2) Gene in Carotenoid Metabolism of the Red Shell Hard Clam (Meretrix meretrix) - Lulu Fu; Heming Shi; Wenfang Dai; Hanhan Yao; Yongbo Bao; Zhihua Lin; Yinghui Dong (Frontiers in Marine Science, 2021)
The relationship between carotenoid and shellfish shell color has gained increasing attention. β, β-carotene-9′,10′-oxygenase 2 (BCDO2) is a key enzyme in animal carotenoid metabolism, and its accumulation affects the change in body color, as demonstrated in mammals, birds, and fish. However, it is unclear whether BCDO2 is involved in the formation of the red shell color of clam. To explore the molecular structure and biological function of BCDO2 gene in the process of carotenoids accumulation, in this study, the BCDO2 from hard clam Meretrix meretrix (designated as Mm-BCDO2 ) was cloned and characterized, and the single-nucleotide polymorphisms (SNPs) associated with shell color were detected. The results of qRT-PCR indicated that Mm-BCDO2 gene was expressed in all six tested tissues, and the expression of mantle was significantly higher than other tissues ( P < 0.05). The association analysis identified 20 SNPs in the exons of Mm-BCDO2 , among which three loci (i.e., c.984A > C, c.1148C > T, and c.1187A > T) were remarkably related ( P < 0.05) to the shell color of clam. The western blot analysis revealed that the expression level of Mm-BCDO2 in the mantle of red shell clams was stronger than that of white shell clams ( P < 0.05). Further, the immunofluorescence analysis indicated that the single-layer columnar cells at the edge of the mantle were the major sites for the Mm-BCDO2 secretion. This study explored the potential impacts of BCDO2 gene on the shell color of M. meretrix , which provided a theoretical basis for a better understanding of the important role of BCDO2 in carotenoid metabolism.